THE FIRST FINDING OF CORUNDUM IN EXSOLUTION STRUCTURES OF OXIDES IN GABBROIC ROCKS FROM THE POLAR URALS - Kulikova K.V.; Varlamov D.A. (My University, 2006)
In the present-day geological structure of the Schuch’ya area in the Polar Urals, the ultramafic and dunite–wehrlite–clinopyroxenite complex (DWC) rocks of the Syumkeu massif (the northernmost ophiolitic massif of the Urals) give way eastward to amphibolites and gabbroic rocks of the Malyko–Kharampe Complex. These rocks belong to the tholeiitic series crystallized from the high-alumina melt. The melt was formed in the backarc-basin setting under the influence of both hydrous fluids released from the subducted plate and the influx of aluminous sediments. The high-alumina gabbroic rocks of the Malyko-Kharampe Complex contain aggregates of Fe–Ti–Al oxides as intergrowths of magnetite, ilmenite, hercynite, and corundum.
Keywords: Polar Urals; corundum